Struktur Pendapatan Rumah Tangga dan Tingkat Kesejahteraan Petani Di Kecamatan Muara Sabak Timur Kabupaten Tanjung Jabung Timur - Evi Adriani; Susilawati Susilawati; Ali Fahmi (Universitas Batanghari, 2021)
This study aims to analyze the structure of household income and the level of welfare of farmers in the sub-sector of food crops and horticulture in Muara Sabak Timur Subdistrict. The survey method using questionnaires was conducted to collect primary data as the main data in this study. The sampling method used is purpossive sampling to determine the sample location and accidental sampling is used to determine the respondents of farmers as many as 40 farmers directly at the site. Data analysis method with descriptive statistics and logistic regression. The results showed that the source of income of farmers' households in Muara Sabak Timur subdistrict is still dominated by the main income from food crops and hortikutura farming even though today almost all farmers have jobs outside the farm as a side job. Variable income and the number of family members have a significant impact on the welfare of farmers in a positive direction while the education of the head of the household has a significant effect with a negative direction.